Surgical Aspects of the Treatment of Patients With Generalized Peritonitis - B. V. Sigua; V. P. Zemlyanoy; S. V. Petrov; V. A. Ignatenko; P. A. Kotkov (Неотложная медицинская помощь, 2021)
BACKGROUND Much attention is currently given to the issues of surgical treatment of common forms of secondary peritonitis, which is associated with unsuccessful results of treatment of this group of patients and the lack of a unified approach to surgical tactics among patients requiring repeated surgical interventions for adequate sanitation of the abdominal cavity.AIM OF STUDY Improvement of the immediate results of treatment of patients with generalized secondary peritonitis by determining the approaches to choosing the optimal surgical tactics.MATERIAl AND METHODS We analyzed the results of treatment of 220 patients with common forms of secondary peritonitis who were treated at the Elizavetinskaya hospital of St. Petersburg in the period from 2013 to 2019. The indicated patients were divided into two groups, comparable in terms of the main features, including the depth pathomorphological changes in the abdominal cavity, assessed by calculating abdominal cavity index (ACI) and the Mannheim peritonitis Index (MPI). The main group consisted of 109 patients, where developed algorithm was used, which supposed planned sanitation relaparotomies within up to 2 days in patients with high values of ACI and MPI. The comparison group included 111 patients who underwent sanitation interventions “on demand”, that is, in the presence of signs of persistence of the infectious process in the abdominal cavity. The results of treatment were compared by assessing the level and structure of postoperative mortality, the frequency of complications, and the length of stay in intensive care units and hospital. Mathematical-statistical dataprocessing, calculations of intensive and extensive coefficients of features, assessment of the statistical significance of differences in features for the studied groups were carried out.RESUlTS The use of a differentiated approach to performing planned relaparotomy in patients with generalized peritonitis made it possible to reduce the overall mortality 1.7-fold (from 51.3 to 30.2%) (p=0.001) due to a decrease in the proportion of abdominal sepsis as a cause of unfavorable the outcome. No significant effect of the use of this algorithm on the frequency and structure of complications, as well as the duration of multiple organ failure, was found.FINDINGS The use of planned relaparotomy among the selected patients helps to reduce postoperative mortality without significantly negatively affecting other treatment results.